(untitled) (Ilm fan taraqqiyotida raqamli iqtisodiyot va zamonaviy ta’limning o’rni hamda rivojlanish omillari, 2025)
Abstract: The thesis examines the distinctions between adequate and equivalent translation, highlighting their specific characteristics and the key aspects relevant to translation processes. It also incorporates insights from prominent experts in the field. Due to the conceptual closeness of adequacy and equivalence, translators may encounter challenges or errors in their work. Achieving adequate translation is particularly complex, as it demands an in-depth understanding of both the source and target languages. The study outlines the primary features of adequate and equivalent translation and discusses various methodologies designed to enhance the accuracy and quality of the translation process.